2010
DOI: 10.1002/app.32041
|View full text |Cite
|
Sign up to set email alerts
|

Role of carboxyl pendant groups of medium chain length poly(3‐hydroxyalkanoate)s in biomedical temporary applications

Abstract: The poly(3-hydroxyoctanoate) (PHO) is a biodegradable polyester containing hydrophobic side chains. One way to obtain more hydrophilic polyester consisted in the introduction of polar groups in the side chains. Carboxyl groups (PHO 75 COOH 25 ) were introduced by chemical modifications. The role of carboxyl groups was investigated in the first part as potential support for cell seeding by studying the cell adhesion and proliferation, and in the second part as potential drug carrier by comparing the abilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…After 72 hours of incubation a decrease of cell viability can be explained by a cytotoxic effect of PHOD-COOH. As described previously a partial reorganization of the polymeric material during the 72 hours of incubation can lead to the presence of carboxylic groups at the surface and an increased hydrophilic surface [33]. As seen earlier bovine serum albumin interacts preferentially with hydrophobic surfaces.…”
Section: Proliferationmentioning
confidence: 80%
See 1 more Smart Citation
“…After 72 hours of incubation a decrease of cell viability can be explained by a cytotoxic effect of PHOD-COOH. As described previously a partial reorganization of the polymeric material during the 72 hours of incubation can lead to the presence of carboxylic groups at the surface and an increased hydrophilic surface [33]. As seen earlier bovine serum albumin interacts preferentially with hydrophobic surfaces.…”
Section: Proliferationmentioning
confidence: 80%
“…These results could be explained by the presence at the film surface of a few quantities of carboxylic groups and PEG graft oligomers, which does not decrease significantly the materials hydrophobicity. Indeed the most probable explanation is the internalization of the polar groups during the film preparation process in chloroform as apolar solvent [33]. Films have been prepared and sterilized under UV-C germicidal lamp in the laminar flow cabinet.…”
Section: Poly(3-hydroxyalkanoate)s Phasmentioning
confidence: 99%
“…The drug release profile of this polymer recorded an increase in doxorubicin release and cell proliferation studies also showed better cell proliferation. 50 In addition to drugs, PHAs were also studied for releasing nucleic acids and proteins; for example; cationic PHA was synthesized to obtain polyIJhydroxyoctanoate)-co-(hydroxy-11-(bisIJ2-hydroxyethyl)amino)-10-hydroxyundecanoate) to immobilize plasmid DNA and its delivery was monitored, 51 and inactive extracellular PHA depolymerase and mcl PHA polyij(3-hydroxyoctanoate)-co-(3-hydroxyhexanoate)] were used for immobilization and delivery of proteins. 52 High performance PHAs were studied as transdermal drug delivery systems (TDDS), which are composed of monomers like 3-hydroxyhexanoic acid and 3-hydroxyoctanoic acid.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…One of the first studies concerning the chemical modification of PHAs started with the production of poly(3-hydroxyoctanoate- co -3-hydroxyundecenoate) (PHOU) that contained unsaturated groups in the side chains [ 10 , 11 ]. The chemical modifications of the unsaturated groups of PHOU have already been reported [ 12 , 13 , 14 , 15 , 16 , 17 ]. The introduction of polar groups, such as hydroxyl, carboxylic and ammonium groups, makes it possible to modify the hydrophilic/hydrophobic balance of the polymer.…”
Section: Introductionmentioning
confidence: 99%